Sustainability in Higher Education for the Global South:: A Conversation across Geographies and Disciplines - Purushothaman, Seema; Ravi, Chitra; Nagendra, Harini; Mathai, Manu; Mundoli, Seema; Joseph, Gladwin; Barna, Stefi; Nawn, Nandan; Golapan, Radha; Bursztyn, Marcel; Padmanabhan, Martina; Duncan, Sally; et al. (Sustainability in Debate, 2016)
A workshop on ‘Sustainability in Higher Education from the vantage of the Global South’ was organized by the Azim Premji University between 12 and 14 January 2015 in Bengaluru, India. Its goal was to explore how sustainability can be integrated into undergraduate, postgraduate and professional courses. The workshop was divided into four sessions with interlinked themes ”“ the first, with a focus on framing sustainability; the second, on integrating sustainability in higher education; the third, on sustainability curricula; and the last, on pedagogy for sustainability. All four sessions were informed by the broader educational goal of enabling students from diverse backgrounds to envision, conceptualise, research and implement sustainability in varied personal and professional contexts. Participants of the workshop drew upon their varied experiences, from India and institutions across the world, in the teaching and learning of the multidimensional concept of sustainability in diverse geographies. The questions, counterquestions, discussions and potential solutions raised during the workshop are presented in this paper in a dialogic style.